An integrated human health risk assessment framework for alkylphenols due to drinking water and crops' food consumption. (June 2023) - Penserini, Luca; Cantoni, Beatrice; Gabrielli, Marco; Sezenna, Elena; Saponaro, Sabrina; Antonelli, Manuela
Abstract: The increasing overexploitation and pollution of freshater resources are potential threats for public health, causing cross-contamination among the interconnected environmental compartments (freshwater, soil, crops). In particular, contaminants of emerging concern (CECs) originating from anthropic activities are not completely removed by wastewater treatments plants. This leads to their presence in drinking water (DW) sources, soil and crops intended for human consumption due to discharges of treated wastewater in surface waters and direct wastewater reuse practices. Currently, health risk assessments are limited to single exposure sources without considering the multiple exposure routes to which humans are subjected. For instance, among CECs, bisphenol A (BPA) and nonylphenol (NP), respectively, adversely affect immune and renal systems and have been frequently detected in DW and food, their major exposure sources for humans. Here, an integrated procedure is proposed to quantitatively assess health risk from CECs due to multiple exposure from the consumption of both DW and food, considering the relevant inter-connected environmental compartments. This procedure was applied to BPA and NP to calculate their probabilistic Benchmark Quotient (BQ), showing its potential in quantitatively apportioning the risk between contaminants and exposure sources, and its use as a decision support tool for prioritizing mitigation measures. Our results indicate that, even though the human health risk due to NP is not negligible, the estimated risk due to BPA is significantly higher, and the consumption of food from edible crops determines a higher risk compared to tap water. Hence, BPA is undoubtedly a contaminant to be prioritized, especially through mitigation actions aimed at its prevention and removal from food. Graphical abstract: Image 1 Highlights: An integrated risk assessment for multiple exposures to contaminants was created. Contaminants exposure comparison between drinking water and crop food was performed. Health risk due to NP is not negligible, but BPA risk is significantly higher. Crops' food intake is the main alkylphenols exposure source compared to tap water. Analytical and data gaps exist on CECs monitoring in interconnected compartments.